Transformational Leadership Versus Strategic Alliances: Unpacking Organizational Adaptation Mechanisms in Jordanian Pharmaceutical Firm - Obeidat, Heba Derar; Zulkiffli, Siti Nur ’Atikah; Padlee, Siti Falindah; Zaki, Nur Amalina Mohamad (International Review of Management and Marketing, 2026)
The role of organizational adaptation in global turbulence is vital to survival but the processes that drive it in the limited emerging market segment are poorly comprehended. This research provides a considerable gap in its exploration of how transformational leadership and strategic alliance affect the organisational adaptation in Jordanian pharmaceutical companies in the presence of top management commitment. The top and middle managers (325) in the sector were surveyed by a quantitative survey and the results were assessed through the partial least squares structural equation modeling (PLS-SEM). The findings indicate that transformational leadership is a very strong indicator of adaptation, and strategy alliances are not significant. Moreover, the best power commitment of top management serves as a strong force in the closeness of management and adaptability and cannot unlock value through alliances. Such results lead to the problem of the classical theory of strategy, which proves internal dynamics of leadership to be a more powerful sustaining mechanism than visiting alliances under strict conditions of regulation. The research contributes as long as there is an original contribution to theory and practice through the specification of the boundary conditions of strategic alliances and the fact that internal governance and leadership orchestration is the essential driver of creating adaptive capacity.